Postoperative Recurrence of Instability After Arthroscopic Bankart Repair for Shoulders With Primary Instability Compared With Recurrent Instability: Influence of Bipolar Bone Defect Size. Issue 1 (January 2020) - Nakagawa, Shigeto; Hirose, Takehito; Uchida, Ryohei; Tanaka, Makoto; Mae, Tatsuo
Background: In shoulders with traumatic anterior instability, a bipolar bone defect has recently been recognized as an important indicator of the prognosis. Purpose: To investigate the influence of bipolar bone defects on postoperative recurrence after arthroscopic Bankart repair performed at primary instability. Study Design: Cohort study; Level of evidence, 3. Methods: The study group consisted of 45 patients (45 shoulders) who underwent arthroscopic Bankart repair at primary instability before recurrence and were followed for at least 2 years. The control group consisted of 95 patients (95 shoulders) with recurrent instability who underwent Bankart repair and were followed for at least 2 years. Glenoid defects and Hill-Sachs lesions were classified into 5 size categories on 3-dimensional computed tomography and were allocated scores ranging from 0 for no defect to 4 for the largest defect. The shoulders were classified according to the total score for both lesions (0-8 points). The postoperative recurrence rate was investigated for each score of bipolar bone defects and was compared between patients with primary instability and patients with recurrent instability. The same analysis was performed for the age at operation (<20 years, 20-29 years, or ≥30 years) and for the presence of an off-track Hill-Sachs lesion. Results: Bipolar bone defects were smaller in shoulders with primary instability (mean ± SD defect score, 1.4 ± 1.5 points) than in those with recurrent instability (3.6 ± 1.9 points) and were larger in older patients than in younger patients at the time of primary instability. The postoperative recurrence rate was low (6.7%) in shoulders with primary instability regardless of the size of the bipolar bone defect and the patient's age, whereas the postoperative recurrence rate was high (23.2%) in shoulders with recurrent instability, especially among patients younger than 20 years with bipolar bone defects of 2 points or greater. An off-track Hill-Sachs lesion was found in only 1 patient in the oldest age group (2.2%) at primary instability, but it was found in 19 patients (20%) at recurrent instability, including 14 patients younger than 30 years. Among patients with an off-track lesion, the postoperative recurrence rate was significantly higher in patients younger than 20 years with recurrent instability (recurrence rates: <20 years, 71.4%; 20-29 years, 14.3%; ≥30 years, 0%). Conclusion: The recurrence rate was consistently low in patients with primary instability and was significantly influenced by bipolar bone defect size and patient age in patients with recurrent instability.